Ecomorphology of the digestive tract of the brazilian electric ray Narcine brasiliensis (Olfers, 1831) (Torpediniformes: Narcinidae) - Marinsek, Gabriela Pustiglione [UNESP]; Viliod, Marcela Coffacci de Lima [UNESP]; Mari, Renata de Britto [UNESP] (Wiley, 2017)
Elasmobranchii shows particular characteristics that make them susceptible to the impacts caused by fishing pressure, especially bottom trawling, which mostly affect rays, as they have demersal habits. Based on food availability and feeding ability, Polychaeta and Sipunculiforme are the bases of Brazilian electric ray Narcine brasiliensis diet. Morphologically, the digestion starts in the oesophagus with acid mucines action. The existence of acid and neutral mucines in the posterior intestine prevents lesions in the mucosa and favours the passage of faeces and shell residues. Thus, this study shows the interaction between their habitat, the organisms and their morphophysiology.
Keywords: diet; digestive system; Elasmobranchii; histochemistry; morphology